“By their fruits you will recognize them”: notes dedicated to Professor Karol Latowski – the prominent Polish botanist - Ilyinska, Antonina P.; Yena, Andriy V.; Mosyakin, Sergei L.; Protopopova, Viera V.; Shevera, Myroslav V. (Biodiversity: Research and Conservation, 2015)
“By their fruits you will recognize them”: notes dedicated to Professor Karol Latowski – the prominent Polish botanist